Landscape culture - culturing landscapes : the differentiated construction of landscapes - Bruns, Diedrich; Kühne, Olaf; Schönwald, Antje; Theile, Simone (RaumFragen: Stadt - Region - Landschaft, Stadt - Region - Landschaft, 2015)
In this book an international group of authors reflects mechanisms of the cultural and social construction of landscapes. International migration and global exchange are associated with a multitude of different cultural meanings of landscapes. The logics of multi-cultural perceptions and meanings of landscape call for trans-disciplinary research, and for guidance on addressing culturally sensitive issues and inclusion in practical planning. Content ·        (International) Concepts of Landscapes, Theory Basis ·        Landscape Perception and Preferences in Multicultural Settings ·        Inter-Acculturation in Multicultural Settings and in Territories in Transition ·        Migrants and Non-Migrants Perception and Preferences ·        A Condition of the Spirit: Mapping Landscape, Language and Culture ·        Current Demands on Landscape Research by the Growing Importance of Hybridization Target Groups ·        Researchers in the Humanities, Social Sciences, Leisure Sciences ·        Landscape architects ·        Urban and landscape planners ·        Urban and regional sociologists The Editors Dr. Diedrich Bruns teaches as professor at the department for landscape architecture at Kassel University. Dr. Olaf Kühne is professor of agricultural- and regional management at the University of Weihenstephan-Triesdorf. Dr. Antje Schönwald is research assistant for geography at the University of Saarland. Dipl.-Ing. Simone Theile is research assistant for landscape planning at Kassel University.